Complexes of Crown Ether Macrocycles with Methyl Guanidinium: Insights into the Capture of Charge in Peptides. Issue 17 (1st August 2018) - Avilés‐Moreno, Juan Ramón; Berden, Giel; Oomens, Jos; Martínez‐Haya, Bruno
Abstract: Crown ethers are well known as modulating agents of protein function and interactions. The action of crown ethers is driven by an alteration of the charged moieties of proteins through the capping of cationic amino acid side chains. This study evaluates the conformational features involved in the binding of crown ethers to the side chain of arginine. For this purpose, isolated complexes of methyl guanidinium with 12‐crown‐4 and 18‐crown‐6 are characterized with infrared action vibrational spectroscopy and quantum chemical computations. The conformational landscapes of the two complexes comprise an extensive ensemble of conformations close in energy. In the 12‐crown‐4 complex, the crown ether has the plane of its backbone approximately perpendicular to that of the guanidinium moiety and coordinates to two or three of its NH δ + bonds. In the 18‐crown‐6 complex, the crown ether backbone is partially folded and tilted with respect to guanidinium and fixes its position in order to facilitate up to a four‐fold coordination in the complex. The access of the complexes to multiple conformations leads to broad band structures in the N−H stretching region of their vibrational spectra. Abstract : Vibrational action spectroscopy and quantum‐chemical modelling indicates that the macrocyle 12‐crown‐4 (12c4) coordinates to two or three NH δ+ bonds at different positions around methyl guanidinium, whereas 18‐crown‐6 (18c6) fixes its position in order to facilitate up to a tetradentate coordination in the complex.